Correlation between Carotid–Cochlear and Sensorineural Hearing Loss: A Cross-Sectional Study - Sekar, Raghul; Alexander, Arun; Krishnan, Nagarajan (Annals of Otology and Neurotology, 2018)
Background Sensorineural hearing loss is a condition with several etiologies and varies with the age of the individual. Carotid–cochlear interval is the minimum distance between basal turn of cochlea and the genu of petrous part of internal carotid artery. It is believed that constant pulsations from carotid can cause fluid pressure changes within the cochlea leading to damage to hair cells causing hearing loss.Objective To study the correlation between carotid–cochlear interval and degree of hearing loss at different frequencies in patients with sensorineural deafness and compare this interval with normal subjects.Methods Seventy cases with sensorineural hearing loss between 18 and 60 years undergoing HRCT temporal bone were grouped together and 70 cases with normal hearing undergoing CT nose and paranasal sinuses were grouped together. Carotid–cochlear interval measured in both the groups was correlated with the degree and frequency of hearing loss and compared with normal subjects.Results The mean carotid–cochlear interval in sensorineural hearing loss and in normal subjects was found to be 1.30 + 0.68 (SD) mm and 1.83 + 0.74 (SD) mm, respectively with p < 0.001. The coefficient of correlation between carotid–cochlear interval and pure tone average in patients with sensorineural deafness was r = −0.740 with p-value < 0.001.Conclusion Carotid–cochlear interval is significantly low in patients with sensorineural hearing loss and bears a strong negative correlation with the degree of hearing loss at mid- and high-frequency ranges. Thus we hypothesize that pulsations from carotid artery cause damage to hair cells in the organ of Corti producing audiological symptoms such as hearing loss.
Keywords: carotid–cochlear interval; cochlear implantation; sensorineural hearing loss